+0  
 
0
696
2
avatar

If S=P(1+rt), make t the subject formula.

1. t= S/r - P/r

2. t= P/Sr - 1/r

3. t= S/r - P/r - 1/r

4. t= S/Pr - 1/r

Guest Sep 14, 2017
 #1
avatar
0

Solve for t:
S = P (r t + 1)

Reverse the equality in S = P (r t + 1) in order to isolate t to the left-hand side.
S = P (r t + 1) is equivalent to P (r t + 1) = S:
P (r t + 1) = S

Divide both sides by a constant to simplify the equation.
Divide both sides by P:
r t + 1 = S/P

Isolate terms with t to the left-hand side.
Subtract 1 from both sides:
r t = (S - P)/P

Solve for t.
Divide both sides by r: 

t = (S - P)/(P r)

Guest Sep 14, 2017
 #2
avatar+87294 
+1

If S=P(1+rt), make t the subject 

 

Divide both sides by P

 

S / P  =  1 + rt       

 

Subtract 1 from both sides

 

S / P  - 1    =  rt     

 

Divide both sides by  r

 

S / (Pr)  - 1 / r   = t

 

 

cool cool cool

CPhill  Sep 14, 2017

7 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.